Metastasis and cancer associated fibroblasts: taking it up a NOTCH - Ghosh, Argha; Mitra, Anirban K. (Frontiers in Cell and Developmental Biology, 2024)
Metastasis is the least understood aspect of cancer biology. 90% of cancer related deaths occur due extensive metastatic burden in patients. Apart from metastasizing cancer cells, the pro-tumorigenic and pro-metastatic role of the tumor stroma plays a crucial part in this complex process often leading to disease relapse and therapy resistance. Cellular signaling processes play a crucial role in the process of tumorigenesis and metastasis when aberrantly turned on, not just in the cancer cells, but also in the cells of the tumor microenvironment (TME). One of the most conserved pathways includes the Notch signaling pathway that plays a crucial role in the development and progression of many cancers. In addition to its well documented role in cancer cells, recent evidence suggests crucial involvement of Notch signaling in the stroma as well. This review aims to highlight the current findings focusing on the oncogenic role of notch signaling in cancer cells and the TME, with a specific focus on cancer associated fibroblasts (CAFs), which constitute a major part of the tumor stroma and are important for tumor progression. Recent efforts have focused on the development of anti-cancer and anti-metastatic therapies targeting TME. Understanding the importance of Notch signaling in the TME would help identify important drivers for stromal reprogramming, metastasis and importantly, drive future research in the effort to develop TME-targeted therapies utilizing Notch.